The multifarious Mr. Banks : from Botany Bay to Kew, the natural historian who shaped the world - Musgrave, Toby (Yale University Press, 2020)
A fascinating life of Sir Joseph Banks which restores him to his proper place in history as a leading scientific figure of the English Enlightenment.